Implementing Good Governance Principles: Administrative Reform in Indonesian Local Government - A.M. Fadli Mappisabbi; A. Noerhayati Amirullah; Nurasia Natsir (Management Dynamics: International Journal of Management and Digital Sciences, 2026)
Good governance has become a crucial framework for improving public sector effectiveness, accountability, and responsiveness to citizens’ needs. In Indonesia, decentralization policies since 1999 have devolved significant authority and resources to local governments, creating both opportunities and challenges in implementing good governance principles. This study examines administrative reform efforts in Indonesian local governments, focusing on progress, challenges, and key success factors. Using a multiple case study design, the research analyzed reform initiatives in six district/city governments with diverse contexts. Data were collected through document analysis, semi-structured interviews with government officials, civil society representatives, and citizens, as well as direct observation of administrative processes conducted between March and November 2024. The study assessed six core principles of good governance: participation, transparency, accountability, effectiveness and efficiency, equity and inclusiveness, and rule of law. The findings reveal variations in implementation across regions, with high-performing governments demonstrating strong leadership commitment, systematic planning, active citizen engagement, and effective monitoring mechanisms. However, challenges persist, including limited capacity, bureaucratic resistance, weak accountability enforcement, and low public participation. Key success factors include visionary leadership, capacity development, strategic partnerships, and institutional strengthening. Policy recommendations emphasize enhancing local capacity, accountability systems, citizen participation, and performance evaluation. Good governance has become a crucial framework for improving public sector effectiveness, accountability, and responsiveness to citizens’ needs. In Indonesia, decentralization policies since 1999 have devolved significant authority and resources to local governments, creating both opportunities and challenges in implementing good governance principles. This study examines administrative reform efforts in Indonesian local governments, focusing on progress, challenges, and key success factors. Using a multiple case study design, the research analyzed reform initiatives in six district/city governments with diverse contexts. Data were collected through document analysis, semi-structured interviews with government officials, civil society representatives, and citizens, as well as direct observation of administrative processes conducted between March and November 2024. The study assessed six core principles of good governance: participation, transparency, accountability, effectiveness and efficiency, equity and inclusiveness, and rule of law. The findings reveal variations in implementation across regions, with high-performing governments demonstrating strong leadership commitment, systematic planning, active citizen engagement, and effective monitoring mechanisms. However, challenges persist, including limited capacity, bureaucratic resistance, weak accountability enforcement, and low public participation. Key success factors include visionary leadership, capacity development, strategic partnerships, and institutional strengthening. Policy recommendations emphasize enhancing local capacity, accountability systems, citizen participation, and performance evaluation.